Renewable energy technologies and resources - Anani, Nader (Artech House power engineering series., 2020)
This exciting new book presents an excellent coverage of renewable energy technologies and resources. The book focuses on photovoltaics, hydro, tidal, wind, and biomass systems. It explains the scientific principles and physical systems used for harvesting and harnessing of renewable resources and makes comprehensive use of worked examples and problems. Readers will also learn how to effectively calculate the cost and payback time for a given renewable energy plant by understanding the factors affecting the cost of generating electricity from a renewable energy system. The book uses a simplified mathematical approach and provides appropriate background material. The ultimate objective of the book is to provide a concise text book for university students on science and engineering courses as well as for professional practitioners.